On some domains of convergence of branched continued-fraction expansions of the ratios of Horn hypergeometric functions H_4 - Dmytryshyn, R.; Lutsiv, I.-A.; Dmytryshyn, M.; Cesarano, C. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 For various conditions imposed on the parameters of the Horn hypergeometric function H_4, we study different domains of convergence of the branched continued-fraction expansions of the ratios of these functions.